Relationship between Sleep Quality and Vertigo Incidence in College Students - Khairunnisah, Sitti Zhaharah; Pratama, Ahmad Ardhani; Ratnawati, Wahida (Newinera Publisher, 2024)
One-third of adults are affected by poor sleep quality. Sleep problems are not only experienced by adults. Knowing the relationship between sleep quality and the incidence of vertigo is very important and urgent because of its very broad impact on health, understanding pathophysiology, clinical development, improving quality of life, as well as education and awareness in the community, especially students. In Indonesia, the prevalence of sleep disorders in adolescents is 62.9%. This study aims to determine the relationship between sleep quality and the incidence of vertigo in students. Literature review using Google Scholar, National Center for Biotechnology Information (NCBI) & Research Science found 9 journals based on inclusion & exclusion criteria. The results of the research is the relationship between sleep quality and vertigo involves a complex interaction between physiological and psychological factors. Physiological effects include disorientation and instability, motor coordination, and physiological stress responses such as cortisol. The psychological effects that can occur are anxiety, depression, decreased concentration, decreased cognitive function, and increased psychological discomfort. Lack of sleep in students makes vertigo symptoms worse. Lack of sleep will make vertigo symptoms worse. It is best to arrange the right sleeping position so that symptoms of vertigo do not occur, because vertigo can occur even in people who have never experienced it. The conclusion is there is a relationship between sleep quality and the incidence of vertigo in students.